Tomato breeding for open ground in the south of Russia - M. R. Engalychev; E. A. Dzhos; A. A. Matyukina; O. V. Verba; E. V. Demidenko; V. S. Sosnov; A. А. Rubtsov (Овощи России, 2024)
Relevance. Tomato is the most widespread vegetable crop in the southern regions of Russia and one of the most popular with the population in all natural and climatic zones of the country. The majority of products is produced in large vegetable-growing, farming and private household farms. One of the most important tasks is to improve the assortment taking into account natural and climatic conditions of cultivation and directions of use. In this regard, the selection of industrial tomato with a high level of flexibility and resistance to biotic and abiotic stressors for the south of Russia is an urgent task.   The aim of the study is to evaluate economically valuable features of perspective lines and new hybrids of tomato of industrial type, adapted to the conditions of southern Russia.   Material and methodology. The work was carried out in the open field conditions of experimental production farm of the Federal Scientific Center of Vegetable Industry (Moscow region) and Biryuchekutskaya vegetable breeding experimental station – branch of the FSBSI FSVC (Rostov region).   The objects of research were breeding material and 6 perspective new hybrid combinations of tomato of selection of the Federal State Budgetary Scientific and Scientific Institution of the Russian Federation.   Results and discussion. As a result of step-by-step study and selection, the most promising samples were identified for further use as source material for practical breeding: B-6-C-2014, VS-B-№7, VS-B-18, VS-B-20, VS-B-35, VS-B-38. As a result of the competitive testing, the best hybrid combinations were identified: F1 B-1, F1 B-2, F1 B-4, meeting the requirements of commercial production in the south of Russia. It is shown that the hybrid combination F1 B-2 exceeds both standard samples F1 Meteor and F1 Perfectpeel both in terms of total yield (by 10.9 t/ha and 9.6 t/ha), marketability of fruits, and dry matter content in fruits (6.1 % vs. 5.1% and 5.2 %). Taking into account the complex of economic characteristics, a precocious F1 hybrid of tomato F1 B-2 called F1 Profy has been submitted to the State Variety Testing, as it shows stable economic characteristics over several years of study.